Formulation of Fiber-Enriched Crackers with Oleaster Powder: Effect on Functional, Textural, and Sensory Attributes - Duskun, Beyzanur; Kutlu, Gozde; Akman, Perihan Kubra; Bekiroglu, Hatice; Tornuk, Fatih (Springer, 2025)
The objective of this study was to produce fiber-enriched crackers by substitution of corn flour and whole wheat flour with oleaster powder (OP) at levels of 0% (C-0), 10% (C-10), 20% (C-20), 30% (C-30), and 50% (C-50) and to determine their sensory, textural, color, and bioactive properties, as well as revealing their dietary fiber and glycemic index values. The results showed that the L* values of the samples were found to range from 62.39 (C-30) to 67.31 (C-0), a* values from 4.43 (C-10) to 8.30 (C-50), and b* values from 21.32 (C-10) to 27.40 (C-50). The hardness and fracturability of the samples decreased with increasing OP concentration, with hardness values ranging from 77.45 to 363.35 N and fracturabilitiy values ranging from 23.30 to 33.90 mm. The total phenolic content (TPC) of the cracker samples ranged from 7.39 to 15.06 mg GAE/100 g, while DPPH radical scavenging activity, CUPRAC antioxidant activity, and FRAP assay values increased with the elevating OP concentration, spanning 4.76 to 93.09 mg TE/100 g, 191.03 to 557.4 mg TE/100 g, and 35.70 to 129.90 mg TE/100 g, respectively. The total dietary fiber content also increased in parallel with the OP level (from 6.83 to 15.15%). The Hydrolysis index values ranged from 109.00 to 74.49%. Although all cracker samples were classified as high glycemic index foods, OP incorporation also decreased the glycemic values up to similar to 19% with values ranging from 80.60 (C-50) to 99.55 (C-0). In conclusion, the addition of OP significantly improved the nutritional properties of the crackers by increasing their dietary fiber, TPC and antioxidant activities as well as decreasing their glycemic index without affecting the sensory attributes. Achieving a balance between nutritional improvement and desirable sensory attributes remains key for optimizing cracker formulations.
Keywords: Oleaster; Crackers; Dietary fiber rich; Glycemic index; Product formulation